Considerazioni costituzionalistico-canoniche a margine del Documento di studio su Primato e sinodalità nei dialoghi ecumenici (Stato, Chiese e pluralismo confessionale, 2024)
Constitutional-canonical considerations on the margins of the Study Document on Primacy and Synodality in Ecumenical DialoguesABSTRACT: The article examines the constitutional-canonical significance of the recent Study Document The Bishop of Rome. Primacy and Synodality in Ecumenical Dialogues and the Encyclical Ut unum sint prepared by the Dicastery for the Promotion of Christian Unity (2024). The first part (general recognitions) describes the overall structure of the Document and highlights the scope of the arguments in favor of primacy and the fundamental principles of ecclesial communion identified, pointing out the main convergences and hermeneutical contrasts. The second part (juridical-exploratory), taking its cue from the usefulness of a juridical reading of the text as well, analyzes the Document's narrow underlying juridical approach, the potentialities and limitations of the levels of the articulation of ecclesial communion (local, regional and universal) and the proposed communal, collegial and personal structure. The substantive insights and openings of ecumenical dialogues overcome methodological and epistemological inadequacies. The good of universal primacy represents a widely recognized and yearned-for value. Ecumenical sensitivity urges the search for a more authoritative and thoughtful form of exercise of the papacy and respect for the flexibility and disciplinary diversification typical of the ecclesial system.SOMMARIO: 1. Una prospettiva di lavoro stimolante - 2. La struttura complessiva del Documento - 3. Gli argomenti a favore del Primato - 4. I principi fondamentali della comunione ecclesiale - 5. Convergenze e contrast ermeneutici - 6. L’utilità di una lettura giuridica “sottotraccia” del Documento - 7. La concezione del diritto ecclesiale - 7.1. L’impostazione di fondo del testo - 7.2. L’argomento giuridico è contrario alla riunificazione? - 8. La percezione dei livelli del mistero ecclesiale - 8.1. L’articolazione della comunione ecclesiale - 8.2. L’interazione universale-particolare - 9. La determinazione della struttura comunitaria, collegiale e personale - 9.1. La positiva emersione della sinodalità - 9.2. Il rischio di un modello o schema formale - 10. La sensibilità e gli spunti ecumenici.